Displacement-controlled nonlinear analysis of RC frames and grids - Shariff, M. Najeeb; Menon, Devdas (Journal of Structural Engineering, 2025)
This paper presents details of a nonlinear analysis program capable of tracing the complete load-deflection response of reinforced concrete (RC) beams, frames and grids. The program has been developed in MATLAB using a displacement-controlled algorithm. The program is capable of handling geometric nonlinearity by using a geometric stiffness matrix in conjunction with a primary stiffness matrix that is constantly updated iteratively. Material nonlinearity is accounted for by making use of prescribed moment-curvature formulations. Stiffness degradation due to cracking of concrete, yielding of steel, tension-stiffening, strain softening and P-Δ effects is incorporated. The program is computationally efficient and requires only minimal input from the user. The proposed methodology has been validated against experimental data. It is seen that the numerical results generated using the proposed algorithm are in good agreement with the experimental results reported in the literature. Further, the method has been extended to RC grids and RC columns in tension.